A kind of alkyd external enamel and preparation method thereof
By using bio-based high flash point alkyd resin and an optimized pigment filler system in alkyd resin coatings, combined with the use of coupling agents, the problem of difficult to take into account both performance and biodegradability in the prior art is solved, and bio-based coatings with high flash point, excellent adhesion and wear resistance are achieved.
Patent Information
- Application Number
- CN202410475125.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-04-19
AI Technical Summary
The existing high-flash point alkyd resin coatings are difficult to balance the performance and biodegradability, and cannot meet higher application needs.
Bio-based high flash point alkyd resin is used as the matrix resin. By optimizing the type and particle size of the pigment filler, and adding coupling agents isocyanate silane and glyceryl ether silane to the system, the pigment filler is modified to improve its compatibility with the alkyd resin and impart excellent adhesion to the coating film.
Bio-based coatings with high flash point, high adhesion, high aging resistance and high wear resistance are prepared to meet the requirements of external magnetic paint. At the same time, the coating is environmentally friendly and safe, and is suitable for the storage and transportation of general chemicals.
Smart Images

Figure BDA0004800261370000031 
Figure BDA0004800261370000071 
Figure BDA0004800261370000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alkyd resin coatings, and in particular relates to an alkyd external enamel and a preparation method thereof. Background Art
[0002] Bio-based materials can be defined as "man-made or artificially processed organic macromolecules extracted from biological resources", mainly used in the fields of plastics and fibers. Their raw materials are renewable resources, which can be biodegradable or non-biodegradable. When degraded, they can return to nature in the form of water, carbon dioxide, inorganic compounds and biomass through composting, and according to ISO and ASTM rules, no toxic and / or distinguishable residues will be left. With the continuous consumption of non-renewable resources, the development and utilization of bio-based materials, which are known for being "green, environmentally friendly, renewable and easily degradable", have received more and more attention.
[0003] Alkyd resin is made by condensation esterification of vegetable oil or unsaturated fatty acid and polyol, polyacid, etc. The synthetic monomer is rich in source, low in price, with many varieties and convenient chemical modification. The source of vegetable oil is sustainable, so alkyd resin is currently the most widely used bio-based coating film-forming material. Since most of the raw materials used in alkyd resin are derived from bio-based materials, the prepared alkyd coating has good gloss, adhesion and other properties, and has the advantages of convenient construction, simple construction environment, and weather resistance, and is widely used in various building materials. Alkyd resin may be 100% bio-based, and its three components (fatty acids, diacids and polyols) can be extracted from natural non-petrochemical resources, which enhances the vitality of alkyd resin as a sustainable and environmentally friendly product.
[0004] Flash point is the lowest temperature at which the vapor formed on the surface of a flammable liquid or solid mixes with air and burns when it encounters an open flame. It is an important physical quantity to measure the flammability of organic compounds and an important basis for classifying the fire hazard of flammable liquids. High flash point coatings are not hazardous chemicals and have good safety. They can be stored and transported like general chemicals. Compared with ordinary solvent-based coatings, they have obvious advantages. High flash point alkyd resins are also widely used in coatings.
[0005] The patent (CN116769146A) discloses a high-flash-point long-acting safe alkyd resin and its preparation and application, which relates to the field of alkyd resins. The alkyd resins include calcite resin, soybean oil acid, arachidic acid, glycerol, neodecanoic acid glycidyl ester, rosin, ionic liquid catalyst, terephthalic acid, benzoic acid, reflux xylene solvent and diluted high-flash-point solvent. The high-flash-point long-acting safe alkyd resin prepared by the invention has the performance of traditional alkyd resins and is suitable for alkyd enamel and alkyd blended paint. It has the advantages of high solid content, low VOC, aging resistance and high stability. It is not a hazardous chemical and can prepare high-flash-point alkyd coatings with a flash point of >61°C (closed cup).
[0006] The patent (CN114479625A) discloses a high flash point alkyd resin protective topcoat, which is made of the following raw materials by mass percentage: high flash point alkyd resin, 50-65%; pigments and fillers, 25-40%; high boiling point environmentally friendly solvent oil, 3-8%; organic bentonite, 0.2-0.6%; anti-settling dispersant, 0.2-0.6%; environmentally friendly composite drying agent, 0.5-1.4%; anti-skinning agent, 0.2-0.4%. The prepared high flash point alkyd resin protective topcoat has the characteristics of high flash point and fast drying, is environmentally friendly, safe, and easy to use, and other properties maintain the advantages of traditional oil-based alkyd paint.
[0007] In the prior art, high flash point alkyd resin coatings do not pay attention to their biodegradability at the same time, and the performance is equivalent to that of ordinary alkyd resins, which cannot meet higher application requirements.
[0008] Based on this, it is necessary to provide an alkyd external enamel, which uses a bio-based high flash point alkyd resin as a base resin, optimizes the type and particle size of pigments and fillers, and adds coupling agents such as isocyanate silane and glycerol ether silane to the system. After grinding, the pigments and fillers can be modified to improve the filling and modification effect of the pigments and fillers. At the same time, the active groups such as isocyanate, epoxy, and hydroxyl in the coupling agent can interact with the alkyd resin to improve the compatibility of the pigments and fillers with the alkyd resin, and give the coating film excellent adhesion to the inorganic substrate. In combination with a high flash point solvent, a bio-based coating with a high flash point, high adhesion, high aging resistance, and high wear resistance can be prepared to meet the use requirements of external enamel. Summary of the invention
[0009] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides an alkyd external enamel and a preparation method thereof. The present invention adopts a bio-based high flash point alkyd resin as a base resin, optimizes the type and particle size of the pigment and filler, and adds coupling agents isocyanate silane and glycerol ether silane to the system. After grinding, the pigment and filler can be modified to improve the filling and modification effect of the pigment and filler. At the same time, the active groups such as isocyanate group, epoxy group, hydroxyl group in the coupling agent can interact with the alkyd resin, improve the compatibility of the pigment and filler with the alkyd resin, and give the coating film excellent adhesion to the inorganic substrate. In combination with a high flash point solvent, a bio-based coating with high flash point, high adhesion, high aging resistance and high wear resistance can be prepared to meet the use requirements of the external enamel. The alkyd external enamel is environmentally friendly and safe, and can be stored and transported according to general chemicals.
[0010] To achieve the above object, in a first aspect, the present invention provides an alkyd exterior enamel paint comprising the following raw materials in parts by weight:
[0011]
[0012]
[0013] The pigment is selected from at least two of nano titanium dioxide, nano zinc oxide and aluminum oxide.
[0014] In a preferred embodiment, the coupling agent is isocyanate silane and glycerol ether silane in a mass ratio of 0.5-1:1.
[0015] In a preferred embodiment, the isocyanate silane is selected from isocyanate propyl triethoxysilane and / or 3-isocyanate propyl trimethoxysilane; and the glyceryl ether silane is γ-glycidyloxypropyl trimethoxysilane.
[0016] In a preferred embodiment, the pigment is a mixture of nano titanium dioxide, nano zinc oxide and aluminum oxide, and the mass ratio of the three is 1:0.8-1.5:1-2.
[0017] In a preferred embodiment, the alumina is nano alumina and micron alumina in a mass ratio of 1:1-1.5.
[0018] In a preferred embodiment, the average particle size of the nano titanium dioxide is 150-400 nm; the average particle size of the nano zinc oxide is 10-100 nm; the average particle size of the nano aluminum oxide is 10-100 nm, and the average particle size of the micron aluminum oxide is 1-20 μm.
[0019] Nano titanium dioxide, nano zinc oxide and aluminum oxide are all spherical white fillers, among which nano titanium dioxide and nano zinc oxide also have excellent anti-aging performance, and the compounding of spherical fillers with different particle sizes can improve their filling effect. The present invention uses nano titanium dioxide, nano zinc oxide and aluminum oxide with different particle sizes for compound use, which can increase the theoretical maximum filling volume fraction, reduce the crowding degree of the filler under the same filling amount, improve the processing fluidity and dispersion uniformity of the filling composite system, improve the filling effect and uniformity of the pigment and filler, and ensure the formation of a complete filling network, thereby improving the covering power, wear resistance and aging resistance of the coating film, and reducing the influence of the pigment and filler on the adhesion.
[0020] Furthermore, the present invention adopts bio-based high flash point alkyd resin as the base resin, optimizes the type and particle size of the pigment and filler, and adds coupling agent isocyanate silane and glycerol ether silane to the system. After grinding, the pigment and filler can be modified to improve the filling and modification effect of the pigment and filler. At the same time, the active groups such as isocyanate group, epoxy group, hydroxyl group in the coupling agent can interact with the alkyd resin to improve the compatibility of the pigment and filler with the alkyd resin, and give the coating film excellent adhesion to the inorganic substrate. With the high flash point solvent, a bio-based coating with high flash point, high adhesion, high aging resistance and high wear resistance can be prepared to meet the use requirements of external enamel. The alkyd external enamel is environmentally friendly and safe, and can be stored and transported according to general chemicals.
[0021] In a preferred embodiment, the anti-sagging aid is organic bentonite.
[0022] In a preferred embodiment, the auxiliary agent includes at least one of a dispersant, a drying agent, an anti-skinning agent, a leveling agent, and a defoaming agent.
[0023] In a preferred embodiment, the dispersant is selected from acrylate dispersants and / or polymerized phosphate dispersants; the drying agent is selected from metal oxides and / or metal salts; the anti-skinning agent is selected from at least one of phenolic compounds, mercapto compounds, and oxime compounds; the leveling agent is polyether-modified polysiloxane; and the defoaming agent is a silicone defoaming agent.
[0024] In a preferred embodiment, the high flash point solvent is selected from at least one of diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, ethylene glycol diacetate, dimethyl succinate, dimethyl glutarate, and dimethyl adipate.
[0025] In a second aspect, the present invention provides a method for preparing the aforementioned alkyd external enamel, comprising the following steps:
[0026] S1: Evenly mix 55%-85% of bio-based high flash point alkyd resin, pigments and fillers, coupling agent and 15%-25% of high flash point solvent and anti-sagging agent to obtain slurry;
[0027] S2: Grinding the slurry obtained in step S1 until the fineness reaches the standard;
[0028] S3: adding the remaining bio-based high flash point alkyd resin, the remaining high flash point solvent and the additive, and stirring evenly to obtain the alkyd exterior enamel.
[0029] In a preferred embodiment, in step S2, the fineness is controlled to be ≤15 μm.
[0030] The beneficial effects of the present invention are:
[0031] 1. The present invention adopts bio-based high flash point alkyd resin as the base resin, and adopts nano titanium dioxide, nano zinc oxide, nano aluminum oxide and micron aluminum oxide with different particle size distributions for compounding, and adds coupling agents isocyanate silane and glycerol ether silane to the system. After grinding, the pigments and fillers can be modified to improve the filling and modification effect of the pigments and fillers. At the same time, the active groups such as isocyanate group, epoxy group, hydroxyl group in the coupling agent can interact with the alkyd resin, improve the compatibility of the pigments and fillers with the alkyd resin, and give the coating film excellent adhesion to the inorganic substrate. In combination with a high flash point solvent, a bio-based coating with high flash point, high adhesion, high aging resistance and high wear resistance can be prepared to meet the use requirements of external magnetic paint.
[0032] 2. The alkyd external enamel of the present invention is environmentally friendly and safe and can be stored and transported as general chemicals. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of the present invention, the present invention is described in more detail below in conjunction with specific embodiments. The present invention is not limited by the following embodiments, and the specific implementation method can be determined according to the technical solution of the present invention and actual conditions.
[0034] It is worth noting that the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0035] The following sources of raw materials or equipment are provided as examples:
[0036] Bio-based high flash point alkyd resin: model ETERKYD 1207-70, purchased from Changxing Materials Industry Co., Ltd.;
[0037] High flash point solvent: dipropylene glycol methyl ether, commercially available.
[0038] Nano titanium dioxide: VK-T200S, average particle size 200nm, purchased from Xuancheng Jingrui New Materials Co., Ltd.; R-996, average particle size 270-300nm, purchased from Changzhou Fengshuo Chemical Co., Ltd.; DXN-TB50, average particle size 100nm, purchased from Darcinon Nanotechnology (Changzhou) Co., Ltd.;
[0039] Nano zinc oxide: JC-J30, average particle size 30 nm, JC-J90, average particle size 90 nm, purchased from Shenzhen Jingcai Chemical Co., Ltd.;
[0040] Nano-alumina: NO-O-005-2, average particle size 30 nm, NO-O-005-1, average particle size 100 nm, purchased from Shanghai Naio Nano Technology Co., Ltd.;
[0041] Micron alumina: DCA-01W, average particle size 1 μm, DCA-10W, average particle size 10 μm, DCA-30W, average particle size 30 μm, purchased from Dongguan Dongchao New Materials Technology Co., Ltd.;
[0042] Organic bentonite: BP-183B, purchased from Tuoyi New Materials (Guangzhou) Co., Ltd.;
[0043] Drier: Composite drier ZHV-68, purchased from Shanghai Shenpu Chemical Technology Co., Ltd.;
[0044] Dispersant: BYK110, commercially available;
[0045] Coupling agent: isocyanate propyl triethoxysilane (IPTS), 3-isocyanate propyl trimethoxysilane; γ-glycidyloxypropyl trimethoxysilane (KH560), commercially available.
[0046] Example 1
[0047] Alkyd exterior enamel is composed of the following raw materials by weight:
[0048] 66 parts of bio-based high flash point alkyd resin, 2 parts of coupling agent (1 part of IPTS, 1 part of KH560), 20.52 parts of pigments and fillers (6 parts of VK-T200S, 5.52 parts of JC-J90, 4 parts of NO-O-005-2, 5 parts of DCA-10W), 0.4 parts of anti-sagging agent, 1.6 parts of drying agent, 0.3 parts of dispersant, and 9.18 parts of high flash point solvent.
[0049] The preparation method steps are as follows:
[0050] S1: 48 parts (72.7%) of bio-based high flash point alkyd resin, pigments and fillers, coupling agent and 2 parts (21.8%) of high flash point solvent and anti-sagging agent are mixed uniformly to obtain a slurry;
[0051] S2: Grind the slurry obtained in step S1 until the fineness reaches the standard (fineness is 15 μm);
[0052] S3: adding the remaining bio-based high flash point alkyd resin, the remaining high flash point solvent and the additive, and stirring evenly to obtain the alkyd exterior enamel.
[0053] Example 2
[0054] Alkyd exterior enamel is composed of the following raw materials by weight:
[0055] 45 parts of bio-based high flash point alkyd resin, 1.5 parts of coupling agent (0.5 parts of 3-isocyanatepropyltrimethoxysilane and 1 part of KH560), 12 parts of pigments and fillers (3 parts of R-996, 4.5 parts of JC-J30, 2 parts of NO-O-005-1, and 2.5 parts of DCA-01W), 0.25 parts of anti-sagging agent, 0.8 parts of drying agent, 0.2 parts of dispersant, and 7 parts of high flash point solvent.
[0056] The preparation method steps are as follows:
[0057] S1: 25 parts (55.6%) of bio-based high flash point alkyd resin, pigments and fillers, coupling agent and 1.2 parts (17.1%) of high flash point solvent and anti-sagging agent are mixed uniformly to obtain a slurry;
[0058] S2: Grind the slurry obtained in step S1 until the fineness reaches the standard (fineness is 15 μm);
[0059] S3: adding the remaining bio-based high flash point alkyd resin, the remaining high flash point solvent and the additive, and stirring evenly to obtain the alkyd exterior enamel.
[0060] Example 3
[0061] Alkyd exterior enamel is composed of the following raw materials by weight:
[0062] 90 parts of bio-based high flash point alkyd resin, 3.8 parts of coupling agent (1.8 parts of IPTS, 2 parts of KH560), 40 parts of pigments and fillers (10 parts of VK-T200S, 10 parts of JC-J90, 10 parts of NO-O-005-2, 10 parts of DCA-10W), 0.8 parts of anti-sagging agent, 3.4 parts of drying agent, 0.6 parts of dispersant, and 18 parts of high flash point solvent.
[0063] The preparation method steps are as follows:
[0064] S1: 72 parts (80%) of bio-based high flash point alkyd resin, pigments and fillers, coupling agent and 4.5 parts (25%) of high flash point solvent and anti-sagging agent are mixed uniformly to obtain slurry;
[0065] S2: Grind the slurry obtained in step S1 until the fineness reaches the standard (fineness is 15 μm);
[0066] S3: adding the remaining bio-based high flash point alkyd resin, the remaining high flash point solvent and the additive, and stirring evenly to obtain the alkyd exterior enamel.
[0067] Comparative Example 1
[0068] Except that the coupling agent is 2 parts of IPTS, the rest is the same as Example 1.
[0069] Comparative Example 2
[0070] Except that the coupling agent is 2 parts of KH560, the rest is the same as Example 1.
[0071] Comparative Example 3
[0072] The same procedures as in Example 1 are followed except that only nano-alumina (9 parts of NO-O-005-2 and 0 parts of DCA-10W) is used.
[0073] Comparative Example 4
[0074] The same procedures as in Example 1 are followed except that only micron-sized alumina (0 parts of NO-O-005-2 and 9 parts of DCA-10W) is used.
[0075] Comparative Example 5
[0076] Except for using DXN-TB50 to replace VK-T200S, the rest is the same as Example 1.
[0077] Comparative Example 6
[0078] Except that DCA-30W is used instead of DCA-10W, the rest is the same as Example 1.
[0079] Test example
[0080] 1. Abrasion resistance test: The abrasion resistance of the paint film was tested according to GB / T 4893.8-1985, 400r, and the loss mass of the paint film was calculated in units of 0.001g. For example, the loss mass of the paint film in Example 1 was 7, which means that the loss mass of the paint film in Example 1 was 0.007g.
[0081] 2. Other properties are tested in accordance with the national standard "GB / T 25251-2010".
[0082] The test results of the embodiments and comparative examples are shown in Table 2:
[0083] Table 2 Test results
[0084]
[0085]
[0086] Note: In the aging test, Examples 1-3 and Comparative Examples 1-6 had no blistering, cracking, peeling, or powdering for 300 hours, but there were obvious differences in discoloration and gloss loss.
[0087] As can be seen from Table 2, the alkyd external enamel prepared by the present invention has excellent adhesion to the substrate, and has excellent hiding power, aging resistance and wear resistance, and can meet the use requirements of external porcelain.
[0088] By comparing Example 1 and Comparative Examples 1-6, it can be seen that the specific type of silane coupling agent, the particle size of aluminum oxide and the particle size of nano-titanium dioxide have a great influence on the adhesion, hiding power, aging resistance and wear resistance of the enamel. This may be because the type of silane coupling agent will affect the dispersion effect of the pigment and the content of the polar group of the paint film, while the particle size of the pigment will affect its filling degree and dispersion effect, thereby affecting the adhesion, hiding power, aging resistance and wear resistance of the enamel. Only by using a limited silane coupling agent and a pigment with a limited particle size can a enamel with excellent comprehensive performance be obtained.
[0089] Specifically, Example 1 uses a combination of isocyanate silane and glycerol ether silane. Compared with Comparative Examples 1-2 which only use isocyanate silane or glycerol ether silane, Example 1 can take into account the dispersion of pigments and fillers, the content of polar groups, and the interaction with alkyd resins, thereby improving the adhesion, hiding power, aging resistance, and wear resistance of the magnetic paint.
[0090] In Example 1, nano-alumina and micron-alumina are used in combination. Compared with Comparative Examples 3-4, which only use nano-alumina and micron-alumina, the filling effect and dispersion uniformity of the pigments and fillers in the system can be effectively improved, thereby improving its hiding power, aging resistance and wear resistance, and facilitating adhesion. In particular, in Comparative Example 3, only nano-alumina is used, and the pigments and fillers in the system are all nano-scale, easy to agglomerate, unevenly dispersed, and similar particle sizes are not conducive to improving the filling effect. Even if nano-alumina has better anti-aging performance than micron-alumina, due to the significant decrease in filling effect and dispersion effect, the final paint film's adhesion, hiding power, aging resistance and wear resistance are significantly deteriorated.
[0091] Comparative Example 5 uses nano titanium dioxide with a smaller particle size. The smaller the particle size of nano titanium dioxide, the lower the hiding power, and it is not conducive to dispersion and filling. Comparative Example 6 uses micron aluminum oxide with a larger particle size. The aluminum oxide particle size is too large, and the compatibility with other pigments and fillers is significantly reduced, and it is not conducive to dispersion. Therefore, compared with Example 1, the adhesion, hiding power, aging resistance and wear resistance of the paint film of Comparative Examples 5-6 are deteriorated.
[0092] It should be noted that the above-described specific embodiments can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. Therefore, although this specification has described the present invention in detail with reference to the embodiments, those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. In short, all technical solutions and changes that do not deviate from the spirit and scope of the present invention should be included in the protection scope of the patent of the present invention.
Claims
1. An alkyd external enamel paint, characterized in that: The following raw materials are included by weight: 40-90 parts of bio-based high flash point alkyd resin; 1-4 parts of coupling agent; 10-40 parts of pigments and fillers; 0.2-0.8 parts of anti-sagging agent; 1-4 parts of additives; 6-20 parts of high flash point solvent; The pigment and filler are selected from nano titanium dioxide, nano zinc oxide and aluminum oxide; The average particle size of the nano titanium dioxide is 150-400nm; The coupling agent is isocyanate silane and glycerol ether silane in a mass ratio of 0.5-1:1; The isocyanate silane is selected from isocyanate propyl triethoxy silane and / or 3-isocyanate propyl trimethoxy silane; the glycerol ether silane is γ-glycidyl ether oxypropyl trimethoxy silane.
2. The alkyd external enamel paint according to claim 1, characterized in that: The pigment is a mixture of nano titanium dioxide, nano zinc oxide and aluminum oxide, and the mass ratio of the three is 1:0.8-1.5:1-2.
3. The alkyd external enamel paint according to claim 1, characterized in that: The aluminum oxide is nano aluminum oxide and micron aluminum oxide in a mass ratio of 1:1-1.
5.
4. The alkyd external enamel paint according to claim 3, characterized in that: The average particle size of the nano zinc oxide is 10-100 nm; the average particle size of the nano aluminum oxide is 10-100 nm, and the average particle size of the micron aluminum oxide is 1-20 μm.
5. The alkyd external enamel paint according to claim 1, characterized in that: The anti-sagging auxiliary agent is organic bentonite.
6. The alkyd external enamel paint according to claim 1, characterized in that: The auxiliary agent includes at least one of a dispersant, a drying agent, an anti-skinning agent, a leveling agent, and a defoaming agent.
7. The alkyd exterior enamel paint according to claim 6, characterized in that: The dispersant is selected from acrylate dispersants and / or polymerized phosphate dispersants; the drying agent is selected from metal oxides and / or metal salts; the anti-skinning agent is selected from at least one of phenolic compounds, mercapto compounds, and oxime compounds; the leveling agent is polyether-modified polysiloxane; and the defoaming agent is a silicone defoaming agent.
8. The alkyd exterior enamel paint according to claim 1, characterized in that: The high flash point solvent is selected from at least one of diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, ethylene glycol diacetate, dimethyl succinate, dimethyl glutarate and dimethyl adipate.
9. The method for preparing the alkyd external enamel paint according to any one of claims 1 to 8, characterized in that: The steps include: S1: Evenly mix 55%-85% of bio-based high flash point alkyd resin, pigments and fillers, coupling agent and 15%-25% of high flash point solvent and anti-sagging agent to obtain slurry; S2: Grinding the slurry obtained in step S1 until the fineness reaches the standard; S3: adding the remaining bio-based high flash point alkyd resin, the remaining high flash point solvent and the additive, and stirring evenly to obtain the alkyd exterior enamel.
10. The preparation method according to claim 9, characterized in that: In step S2, the fineness is controlled to be ≤15 μm.
Citation Information
Patent Citations
High-flash-point alkyd resin protective finish paint
CN114479625A
High-flash-point long-acting safe alkyd resin as well as preparation and application thereof
CN116769146A
Alkyd protective paint with high solid content and low VOC content and preparation method thereof
CN111944399A
Water-based EAU protective plate and preparation method thereof
CN117659472A
Cited By
Self-drying acrylic enamel paint and preparation method thereof
CN120944442A
A self-drying acrylic magnetic paint and a preparation method thereof
CN120944442B